Bacteriophage S6 requires bacterial cellulose for Erwinia amylovora infection. (15th March 2022) - Knecht, Leandra E.; Heinrich, Nadine; Born, Yannick; Felder, Katja; Pelludat, Cosima; Loessner, Martin J.; Fieseler, Lars
Summary: Bacteriophages are highly selective in targeting bacteria. This selectivity relies on the specific adsorption of phages to the host cell surface. In this study, a Tn5 transposon mutant library of Erwinia amylovora, the causative agent of fire blight, was screened to identify bacterial receptors required for infection by the podovirus S6. Phage S6 was unable to infect mutants with defects in the bacterial cellulose synthase operon ( bcs ). The Bcs complex produces and secretes bacterial cellulose, an extracellular polysaccharide associated with bacterial biofilms. Deletion of the bcs operon or associated genes ( bcsA, bcsC and bcsZ ) verified the crucial role of bacterial cellulose for S6 infection. Application of the cellulose binding dye Congo Red blocked infection by S6. We demonstrate that infective S6 virions degraded cellulose and that Gp95, a phage‐encoded cellulase, is involved to catalyse the reaction. In planta S6 did not significantly inhibit fire blight symptom development. Moreover, deletion of bcs genes in E . amylovora did not affect bacterial virulence in blossom infections, indicating that sole application of cellulose targeting phages is less appropriate to biologically control E . amylovora . The interplay between cellulose synthesis, host cell infection and maintenance of the host cell population is discussed.